CRITICAL RACE THEORY-INFUSED CURRICULA TRANSFORMATION IN SOUTH AFRICAN INSTITUTIONS OF HIGHER LEARNING - Sibanda, Omphemetse S (PEOPLE: International Journal of Social Sciences, 2017)
This article seeks to situate curriculum transformation in the South African learning environment on the landscape of critical race theory. The article acknowledges that the need for curriculum transformation in South Africa is a matter beyond any contestation. However, it argues that what has been lacking to date is the absolute resolve on the theory or philosophy that underpins the transformation agenda – which to a certain extent has reduced curriculum transformation to superficial infusion of the principles and values of uBuntu in the curricular; and the drive towards decolonisation of the curricular without much tangible alternative being offered. As part of the execution of the study in this article the author critically examines the literature on critical race theories critical the theory, and examines the applicability of this theory as the bar that underpins curriculum transformation. The researcher contextualises this article with reference to curriculum development agenda at the College of Law of the University of South Africa where he is an academic in the discipline of law.